Corrosion resistance and antibacterial properties of copper coating deposited by cold gas spray - da Silva, F. S. [UNESP]; Cinca, N.; Dosta, S.; Cano, I. G.; Guilemany, J. M.; Caires, C. S.A.; Lima, A. R.; Silva, C. M.; Oliveira, S. L.; Caires, A. R.L.; Benedetti, A. V. [UNESP] (Elsevier, 2019)
This work describes the morphology, corrosion resistance, and antibacterial performance of copper coating deposited onto carbon steel by cold gas spray (CGS). Cross-sectional images of the coating showed a dense microstructure, with porosity lower than 1%. XRD analysis revealed no oxides or phases different to pure copper. The results of electrochemical tests demonstrated the efficient barrier properties and the compact microstructure of the coating, which protected the substrate against corrosion in chloride solution for >1000 h. The copper coating was effective as an antimicrobial agent for inhibiting the growth of Staphylococcus aureus, with bacterial growth being completely inhibited after 10 min of direct contact between the bacteria and the coating surface.
Keywords: Antibacterial surface; Cold gas spray; Copper; Metallic coating; Staphylococcus aureus